Delincuencia común en Chile - Cooper Mayr, Doris (Lom Ed., 1994)
"Combining survey data with in-depth interviews with prisoners, book provides useful analysis of delinquency patterns in Chile. Distinguishes five patterns of criminal behavior that are shaped by ethnicity, gender, and urban/rural residence. Carefully delineates social norms characterizing criminal culture of Santiago"--Handbook of Latin American Studies, v. 57